2022
DOI: 10.1186/s12909-022-03967-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of PRISM and numeric scale for self-assessment of learning progress during a clinical course in undergraduate dental students

Abstract: Objectives To compare Pictorial Representation of Illness and Self-Measure (PRISM) and a numeric scale for self-reflection in dental students. Methods Fourth year dental students were randomly assigned to each receive one interview based on PRISM or a numeric scale to self-assess their competencies at the beginning (t1), the middle (t2) and the end (t3) of integrated clinical course. Questionnaires were used to assess self-perceived benefit of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Although PRISM has been used in previous studies in the dental education context [ 8 , 9 ], there are still limited data on this method in the context of teaching. In a previous study, PRISM was found to be reproducible and sensitive against changes in teaching and that there are significant differences in perceived knowledge and skills between third-, fourth-, and fifth-year dental students ( n = 10 each) [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although PRISM has been used in previous studies in the dental education context [ 8 , 9 ], there are still limited data on this method in the context of teaching. In a previous study, PRISM was found to be reproducible and sensitive against changes in teaching and that there are significant differences in perceived knowledge and skills between third-, fourth-, and fifth-year dental students ( n = 10 each) [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…For clinical implementation, PRISM could be used for self-reflection of the students regarding their learning progress. Thereby, PRISM can be applied during a clinical course in dentistry for a continuous self-reflection of perceived learning progress [ 9 ]. Furthermore, it can be used during a preclinical course to reflect the development of skills during different modules or teaching events [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations